2018
DOI: 10.1136/bmjopen-2017-017079
|View full text |Cite
|
Sign up to set email alerts
|

Ability of postoperative delirium to predict intermediate-term postoperative cognitive function in patients undergoing elective surgery at an academic medical centre: protocol for a prospective cohort study

Abstract: IntroductionPostoperative delirium (POD) is a common complication in elderly patients, characterised by a fluctuating course of altered consciousness, disordered thinking and inattention. Preliminary research has linked POD with persistent cognitive impairment and decreased quality of life. However, these findings maybe confounded by patient comorbidities, postoperative complications and frailty. Our objective is to determine whether POD is an independent risk factor for persistent impairments in attention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Postoperative delirium (POD) is a common complication of the central nerve system after surgical operations in elderly patients, usually characterized by a fluctuating course of altered consciousness, disordered thinking, and inattention [1]. The incidence of POD is 4% to 65% among adult noncardiovascular surgical patients, 35% to 65% in patients undergoing hip fracture surgery, and 9% to 15% in patients receiving elective orthopedic surgery [2].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative delirium (POD) is a common complication of the central nerve system after surgical operations in elderly patients, usually characterized by a fluctuating course of altered consciousness, disordered thinking, and inattention [1]. The incidence of POD is 4% to 65% among adult noncardiovascular surgical patients, 35% to 65% in patients undergoing hip fracture surgery, and 9% to 15% in patients receiving elective orthopedic surgery [2].…”
Section: Introductionmentioning
confidence: 99%
“…17 Further validation of initiatives around frailty assessment to ascertain readiness for surgical treatment or guide perioperative treatment are ongoing. 27 Presumably, mitigating the incidence and extent of PND through these initiatives in individuals deemed to be at higher risk may reduce expenditure and merits consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively recent advancements in the study of aging have led to the concept of the frailty syndrome, a state of depleted physiologic reserve and clinical risk that is associated with, but variably present with, advancing age . Further validation of initiatives around frailty assessment to ascertain readiness for surgical treatment or guide perioperative treatment are ongoing . Presumably, mitigating the incidence and extent of PND through these initiatives in individuals deemed to be at higher risk may reduce expenditure and merits consideration.…”
Section: Discussionmentioning
confidence: 99%
“…This diagnostic scale is known to be superior to other similar tests because it is short, easy-to-understand, and based on simple scoring system [11]. It has been also shown that BOMC test has a high sensitivity rate in detecting cognitive dysfunction [19]. The other potential pitfall of the previous studies is the variable demographic characteristics of the patient cohorts.…”
Section: Discussionmentioning
confidence: 99%